Metabolite Profiles and Antioxidant Activity of Caulerpa racemosa with Different Handlings - sihono, Sihono; Tarman, Kustiariyah; Madduppa, Hawis; Januar, Hedi Indra (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2018)
Â Metabolite profiles and antioxidant activity of Caulerpa racemosa extract with different handlings were investigated. Three different handlings during transportation were applied, namely samples chilled with ice, stored in liquid nitrogen and soaked in seawater. The different handling significantly affected the yield of ethanolic crude extracts and inorganic fractions but insignificantly to organic fractions. Different handlings resulted in differences of major fractions of C. racemosa extracts. Major fractions of the sample that was handled with chilling temperature contained low polar fractions (K10, K11, K12, and K13), while seawater handling extract contained very polar (K1, K2 and K3), polar (K6, K7, and K8) and low polar (K13) fractions. The extract of the sample handled in liquid nitrogen contained balanced fractions. Chilling temperature handling produced highest antioxidant activity (IC50 below 2,000 ppm) in ethanolic extract of C. racemosa. Keywords: antioxidant activity, Caulerpa racemosa, ethanolic extract,handlings, IC50